The Effectiveness Teaching Big Class By Making Group Based on Listening Learning Strategies (Cognitive and Metacognitive) - Wijaya, Sulton Dedi; Yunianti, Sofi (International Journal for Educational and Vocational Studies, 2019)
This research attempts to identify the effectiveness of grouping based on listening strategies in big class. The data were collected from fourth semester students in the form of opinions. The data were analyzed by questionnaire in order to find out the effectiveness of making group based on listening strategies. The questionnaire has three sections, the first section asks about students opinion about listening class and making group in listening class, the second part about the effectiveness of making group in class and the last is about students opinion how to build effectiveness in listening class. The results presented in first section of questionnaire that the students like listening class and making group but the number is only slightly bigger than dislike. The second parts, the students respond that they satisfy enough in making group in listening class. The last section, the questionnaire investigates students opinion about how to build the effectiveness in listening class. The highest answer is building knowledge and work collaboratively. Based on the students answer it is reflected that they tend to prefer work in group for achieving the effectiveness in teaching big class.